DESCRIPTION OF ADOLESCENT LEVEL KNOWLEDGE ABOUT THE ACUTE KIDNEY FAILURE PREVENTION IN ADOLESCENT AT BUMIREJO VILLAGE - Achmad Syaifudin; Slamet Riyanto; Siti Rochjani (Jurnal Ilmiah Keperawatan, 2023)
Background: Acute kidney failure (ARF) is a clinical syndrome characterized by rapidly declining kidney function which causes rapidly developing azotemia. Cases of acute kidney failure that attack children aged 6 months-18 years continue to increase and are dominated by ages 1-5 years. Objective: Describing the level of knowledge about the prevention of acute kidney failure in adolescents at Bumirejo Village, Demak Regency. Method: This research is descriptive quantitative research. Number of samples 35 respondents used a saturated sampling technique. The research instrument used a questionnaire with 20 questions. Results: The results showed that the majority of respondents aged 16-17 years were 10 respondents (28.6%), the majority were senior high school, 14 respondents (40%), the gender of the majority is female, 19 respondents (54.3%). The knowledge about the prevention of acute kidney failure was obtained in the sufficient category (60%). Conclusion: The higher the education of adolescents can help their knowledge.